2012
DOI: 10.1111/j.1442-2042.2012.03225.x
|View full text |Cite
|
Sign up to set email alerts
|

Pathophysiology of urinary incontinence in murine models

Abstract: Urethral closure mechanisms under stress conditions consist of passive urethral closure involving connective tissues, fascia and/or ligaments in the pelvis and active urethral closure mediated by hypogastric, pelvic and pudendal nerves. Furthermore, we have previously reported that the active urethral closure mechanism might be divided into two categories: (i) the central nervous control passing onto Onuf's nucleus under sneezing or coughing; and (ii) the bladder-to-urethral spinal reflex under Valsalvalike st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 34 publications
(91 reference statements)
2
13
0
Order By: Relevance
“…In a previous study, the sneeze‐induced LPP increased by 12.8 cmH 2 O after injection of a 5‐HT2b/2c agonist in VD rats . Our results demonstrated that descending bulbo‐spinal serotonergic pathways enhance the activity of spinal excitatory interneurons in Onuf's nucleus via the 5‐HT2c receptor to promote active urethral closure …”
Section: Discussionsupporting
confidence: 63%
See 3 more Smart Citations
“…In a previous study, the sneeze‐induced LPP increased by 12.8 cmH 2 O after injection of a 5‐HT2b/2c agonist in VD rats . Our results demonstrated that descending bulbo‐spinal serotonergic pathways enhance the activity of spinal excitatory interneurons in Onuf's nucleus via the 5‐HT2c receptor to promote active urethral closure …”
Section: Discussionsupporting
confidence: 63%
“…7 Our results demonstrated that descending bulbo-spinal serotonergic pathways enhance the activity of spinal excitatory interneurons in Onuf's nucleus via the 5-HT2c receptor to promote active urethral closure. 4 We found that A-URE was significantly lower in VD rats than in normal rats, and the LPP in response to manual compression was also significantly lower in VD rats compared to normal rats. The urethral pressure is mediated by contraction of the external urethral sphincter and the pelvic floor muscles under control of the pudendal nerves and somatic nerves.…”
Section: Discussionmentioning
confidence: 53%
See 2 more Smart Citations
“…Both Kamo et al and Constantinou described several clinical findings supporting this mechanism: urethral pressure increase starts before cough transmission, is higher than the intravesical pressure increase, and is reduced by bilateral pudendal blockade . The active closure reflex consists of two parts …”
Section: Physiology Of Urethral Closurementioning
confidence: 94%